Problem of universals of Christianities and differentia specifica of its life are in history (Part II - Byzantium versus Rome) - Pasko, Ihor (Skhid, 2013)
In the article an author continues to reason above the problems of Christianity as spiritual universals and shows the specific of objective this phenomenal in a historical process. In the offered part of secret service attention is concentrated on the general contours of correlation of Christian idea and practice of her embodiment in Byzantium and Roman civilizations.